Evaluation of tensile and flexural properties of woven glass fiber/epoxy laminated composites oriented in edgewise and flatwise directions - Kareem Al-Adily; Mushtaq Albdiry; Haider Ammash (Ain Shams Engineering Journal, 2023)
In this study, the tensile and flexural properties of skin-core-skin woven glass fiber/epoxy laminated composites were conducted. Six plies (laminae) for the skins and twenty-four plies for the core were hand-laid up. All plies used had the same dimensions and the same elastic strength where the skins’ plies kept in flatwise direction while the core’s plies oriented in edgewise and flatwise to study the effect of plies alignments and hence loading direction i.e., edgewise (in-plane) and flatwise (out-of-plane) on the materials characteristics. It was observed that the composites oriented in edgewise position had the highest strength of 186 MPa (enhancement 59%) and deformed at higher loads with minor displacements compared to the flatwise strength of 117 MPa. The SEM analysis of the tensile’s fracture surface showed two dominant toughening mechanisms are debonding (fiber pullout) and fiber breakage, while interlaminar/intralaminar delaminated yarns was observed in the flexural fracture surface.